High glucose reduces Nrf2-dependent cRAGE release and enhances inflammasome-dependent IL-1β production in monocytes: the modulatory effects of EGCG - Chi-Hao Wu; Yin-Hsuan Chang; Chin-Lin Hsu; Sheng-Yi Chen; Gow-Chin Yen (Food Science and Human Wellness)
Soluble receptor for advanced glycation end products (sRAGE) acts as a decoy sequestering of RAGE ligands, thus preventing the activation of the ligand-RAGE axis linking human diseases. However, the molecular mechanisms underlying sRAGE remain unclear. In this study, THP-1 monocytes were cultured in normal glucose (NG, 5.5 mmol/L) and high glucose (HG, 15 mmol/L) to investigate the effects of diabetesrelevant glucose concentrations on sRAGE and interleukin-1β (IL-1β) secretion. The modulatory effects of epigallocatechin gallate (EGCG) in response to HG challenge were also evaluated. HG enhanced intracellular reactive oxygen species (ROS) generation and RAGE expression. The secretion of sRAGE, including esRAGE and cRAGE, was reduced under HG conditions, together with the downregulation of a disintegrin and metallopeptidase 10 (ADAM10) and nuclear factor erythroid 2-related factor 2 (Nrf2) nuclear translocation. Mechanistically, the HG effects were counteracted by siRAGE and exacerbated by siNrf2. Chromatin immunoprecipitation results showed that Nrf2 binding to the ADAM10 promoter and HG interfered with this binding. Our data reinforce the notion that RAGE and Nrf2 might be sRAGE-regulating factors. Un der HG conditions, the treatment of EGCG reduced ROS generation and RAGE activation. EGCG-stimulated cRAGE release was likely caused by the upregulation of the Nrf2-ADAM10 pathway. EGCG inhibited HG-mediated NLRP3 inf lammasome activation at least partly by stimulating sRAGE, thereby reducing IL-1β release.